Atmospheric Black Carbon along a Cruise Path through the Arctic Ocean during the Fifth Chinese Arctic Research Expedition - Jie Xing; Lingen Bian; Qihou Hu; Juan Yu; Chen Sun; Zhouqing Xie (Atmosphere, 2014)
From July to September 2012, during the fifth Chinese National Arctic Research Expedition (CHINARE), the concentrations of black carbon (BC) aerosols inside the marine boundary layer were measured by an in situ aethalometer. BC concentrations ranged from 0.20 ng∙m−3 to 1063.20 ng∙m−3, with an average of 75.74 ng∙m−3. The BC concentrations were significantly higher over the mid-latitude and coastal areas than those over the remote ocean and high latitude areas. The highest average concentration was found over offshore China (643.44 ng∙m−3) during the cruise, while the lowest average was found over the Arctic Ocean (5.96 ng∙m−3). BC aerosol was found mainly affected by the terrestrial input and displayed seasonal and spatial variations. Compared with the results from the third and fourth CHINARE of summer 2008, and summer 2010, the inter-annual variation of BC over the Arctic Ocean was negligible.